The CAT Project - Barua, S. K. (Samir K.) ([London] : SAGE, 2016)
The case provides an opportunity to students to learn about the basic concepts in Project Management using a situation that can be easily understood by all. The case provides the instructor an opportunity to demonstrate to the students as to how precedence relationships are to be generated from assertions made about a project by the project in-charge - a feature that is generally missing in most cases on the subject. The case also provides an opportunity to develop a Linear Programming (LP) model for the project.
Originally Published in: Barua, S. K. (2015). The CAT Project. PROD0306. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Project management -- Case studies